Bio-Inspired Soft Robotics: Design, Fabrication and Applications - Yong Zhong; Pei Jiang; Yi Sun (Biomimetics)
The field of soft robotics has witnessed a remarkable surge in interest and innovation over the past decade, with bio-inspiration playing a pivotal role in driving forward the design, fabrication, and applications of these adaptable and resilient robotic systems [...]